2014
DOI: 10.4236/as.2014.54035
|View full text |Cite
|
Sign up to set email alerts
|

Rice Green Revolution and Climatic Change in East Africa: An Approach from the Technical Efficiency of Rainfed Rice Farmers in Uganda

Abstract: In East Africa where a drastic improvement in food security is an urgent need, rice, a non-traditional crop in most of countries in the region, has emerged as an important food crop that could extend the Green Revolution to the region following the introduction of New Rice for Africa (NERICA) in the early 2000s. Using data collected through a nationwide survey, this paper examines the possibility of rice green revolution by estimating the technical efficiency (TE) of rainfed rice farmers in Uganda and simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In 3.1, low WUE in South East China, South, and South East Asian countries, such as India, Philippines, and Vietnam, several provinces with high rice WUE are mainly located in the northern part of China. Geographically, the WUE situation can be influenced by different climatic factors, such as rainfall and temperature, and it also shows that rice is vulnerable to climate change, which is the uncertainty of future climate change (Aven & Renn, 2015; Barnwal & Kotani, 2013; Buytaert et al, 2010; Maruyama et al, 2014). In the study of global status rice WUE, we found that flood irrigation is still routinely used in most countries today, which requires a certain amount of rainfall as well as irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…In 3.1, low WUE in South East China, South, and South East Asian countries, such as India, Philippines, and Vietnam, several provinces with high rice WUE are mainly located in the northern part of China. Geographically, the WUE situation can be influenced by different climatic factors, such as rainfall and temperature, and it also shows that rice is vulnerable to climate change, which is the uncertainty of future climate change (Aven & Renn, 2015; Barnwal & Kotani, 2013; Buytaert et al, 2010; Maruyama et al, 2014). In the study of global status rice WUE, we found that flood irrigation is still routinely used in most countries today, which requires a certain amount of rainfall as well as irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have examined the linkages and consequences of climate change and food security at various spatial scales [10][11][12][13][14][15][16][17][18][19]. Climate change affects food security in complex ways, which affects food production directly through changes in agroecological conditions and indirectly by affecting the growth and distribution of incomes, thus creating demand for agricultural produce [9,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the method of cultivation, the efficient of production input usage also very determines the production of rice farming (Hormozi et al, 2013;Ojogho and Alufohai, 2010;Wen et al, 2011;Maruyama et al, 2014;Watkins et al, 2014). The effort of rice production increasing through the efficiency of input usage became the right choice.…”
Section: Introductionmentioning
confidence: 99%